Comprehensive scoping review of palliative care development in Africa: recent advances and persistent gaps - Bastos, Fernanda; Garralda, Eduardo; Montero, Alvaro; Rhee, John Y.; Arias-Casais, Natalia; Luyirika, Emmanuel; Namisango, Eve; Pereira, José; Centeno, Carlos; Tripodoro, Vilma A. (Frontiers in Health Services, 2024)
Worldwide 56·8 million people need palliative care (PC), and Africa shows the highest demand. This study updates the 2017 review of African PC development, using a scoping review methodology based on Arksey and O'Malley's framework and the PRISMA-ScR checklist. The review was conducted across PUBMED, CINAHL, Embase, government websites, and the African PC Association Atlas, from 2017 to 2023, charting its progress using the new WHO framework for PC Development, which, in addition to Services, Education, Medicines, and Policies, two new dimensions were incorporated: Research and Empowerment of people and Communities. Of the 4.420 records, 118 met the inclusion criteria. Findings showed increased adult specialised services (n = 675), and 15 of 54 countries have paediatric services. Nonetheless, the ratio of services per population mostly remains under 0,10 per 100.000 inhabitants. PC education was included in undergraduate curricula in 29 countries; despite the rise in morphine availability (28 countries), median consumption remains under 3 mg/per capita/year, and 14 countries presented stand-alone policies. Publications on PC development increased, and 26 countries have National PC Associations. Notwithstanding progress since 2017, significant hurdles remain, highlighting the need for ongoing research and policy development to ensure equitable access to palliative care in Africa.